Marion L. Matics. Entering the Path of Enlightenment. The Bodhicaryāvatāra of the Buddhist poet Sāntideva. George Allen & Unwin Ltd. Londres, 1971. 318 pp. - D., S. (Estudios de Asia y África, 1973)
-